Identity Constructions. Roots and Projections of Studies on Learner Identity: Contributions to Educational Research and Practice (London Journal of Research In Humanities and Social Sciences, 2023)
The work shows the potentiality of the identity construct to integrate personal and contextual aspects in the study of learning, as well as the way in which both influences are combined in the construction of the learner’s identity. The most accepted definition of learner identity highlights its constructive nature: people construct their identity as learners through the meaning and value that they attribute to their experiences of participation in various contexts of learning. The writing attends to the most relevant antecedents in the development and diffusion of these ideas, highlights the current contributions about the distinctive characteristics of the process of construction of learner identity and establishes guidelines regarding the contributions and projections of the new construct for research and design of educational contexts.
Keywords: russia; transit potential; transport; logistics; the Belt and Road initiative; Central Asia; Red Rose; White Rose; feminist translation theory; gender differences; Educational Psychology; Educational environment; Feedback; Socio emotional learning